Management of adult intralobar pulmonary sequestration: A novel approach - Battal O Aldosary; Yasser M Aljehani; Nawal I Algubaisi; Yahya A. A. Sabaah; Khaled M Alkattan (Saudi Journal of Medicine and Medical Sciences, 2014)
Pulmonary sequestration is a known congenital pulmonary malformation. It has been classified into intralobar and extralobar types. We report a case of a symptomatic adult intralobar pulmonary sequestration which was managed in a rather unconventional approach. Such an approach, arterial embolization, has clearly shown to be safe with good outcome in infants and pediatric population. The patient made a full recovery with good outcome. Such case reports show feasibility and safety of embolization as a less invasive management option for adult pulmonary sequestration.